2014
DOI: 10.3390/molecules19055777
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Illumina Sequencing for the Development of 95 Novel Polymorphic EST-SSR Markers in Common Vetch (Vicia sativa subsp. sativa)

Abstract: Abstract:The common vetch (Vicia sativa subsp. sativa), a self-pollinating and diploid species, is one of the most important annual legumes in the world due to its short growth period, high nutritional value, and multiple usages as hay, grain, silage, and green manure. The available simple sequence repeat (SSR) markers for common vetch, however, are insufficient to meet the developing demand for genetic and molecular research on this important species. Here, we aimed to develop and characterise several polymor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 20 publications
5
29
0
Order By: Relevance
“…The decreased levels of polymorphism may be due to the smaller number or close geographic origin of the materials used in the study 12 . In the present study, 112 EST-SSR variations were found in the coding regions, whereas five were found in genes not associated with known proteins, which is similar to the location of EST-SSR markers in common vetch 15 .…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The decreased levels of polymorphism may be due to the smaller number or close geographic origin of the materials used in the study 12 . In the present study, 112 EST-SSR variations were found in the coding regions, whereas five were found in genes not associated with known proteins, which is similar to the location of EST-SSR markers in common vetch 15 .…”
Section: Discussionsupporting
confidence: 80%
“…To date, many SSRs have been developed in many plants through Illumina sequencing; these plants include alfalfa 13 14 , Vicia sativa 15 , and Indian sesame 16 . However, in the genus Elymus , the applications of SSRs have only been presented in a few species, including E. alaskanus 5 , E. caninus 17 , E. trachycaulus 18 , and E .…”
mentioning
confidence: 99%
“…Previous research reported that the occurrence of SSR in the coding regions seems to be limited by non-perturbation of ORFs [ 44 ], and the tri- and hexa-nucleotide repeats are dominant in protein-coding exons of all taxa [ 45 ]. Besides, the relative proportions of EST-SSR motif types observed in this study coincided with previous reports, such as the vetch ( Vicia sativa ) [ 46 ], Ma bamboo ( Dendrocalamus latiflorus ) [ 47 ] and alfalfa ( Medicago sativa ) [ 48 ]. Furthermore, since we found that Vicia cDNA-SSRs are highly polymorphic, thus, those retrieved cDNA-SSR, through the NGS sequencing technology, will be a valuable resource for research communities of the vetch breeding program.…”
Section: Discussionsupporting
confidence: 91%
“…The results from this study suggested that short reads from Illumina/Solexa sequencing can effectively be assembled through “Trinity” giving the advantage of a high assurance and reliable assembly of putative unigenes, including potential and valuable splice variant information. Therefore, de novo sequencing and assembly of transcriptomes or genomes has effectively been utilized for model [ 57 , 58 ] and non-model organisms [ 59 , 60 , 61 ].…”
Section: Resultsmentioning
confidence: 99%